The effectiveness of propolis extract in reducing dentin hypersensitivity: A systematic review - Tavares, Johnny Alexandre Oliveira; da Silva, Francilene Amaral; Santos, Tito Marcel Lima; Caneppele, Taciana Marco Ferraz [UNESP]; Augusto, Marina Gullo (Elsevier, 2021)
Objective: This systematic review was performed to evaluate the effectiveness of propolis on dentin hypersensitivity reduction. Design: The search was conducted in Pubmed, Scopus, Web of science, Latin American and Caribbean Health Sciences Literature data base (Lilacs), Brazilian Library in Dentistry (BBO), Embase, and Cochrane Library aiming to identify relevant randomized clinical trials that evaluated the effect of propolis on dentin hypersensitivity. The Cochrane Collaboration tool was used for assessing the risk of bias. Results: From the total of 63 articles found in the search, six clinical trials were selected. All studies reported that propolis was more effective in reducing hypersensitivity than the placebo. No side effects were observed. Conclusions: Overall, propolis extract can be considered an effective, safe and low-cost alternative to reduce the dentin hypersensitivity.
Keywords: Dentin hypersensitivity; Dentin sensitivity; Propolis; Systematic review